Geochemical assessment of heavy elements in sediments of main Wadis of Western Part of Mosul City, Iraq - Al-Dabbagh, Ali H.; Al-Youzbakey, Kotayba T. (Italian journal of engineering geology and environment, 2021)
<span style="font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; caret-color: #000000; color: #000000; font-size: 8pt; font-family: Arial;" data-sheets-value="{"1":2,"2":"To assess the quality of sediment as it is an essential environmental indicator of water contamination due to sediments represent a permanent or temporary trap for various pollutants, a geochemical study was performed for sediments of four main wadis (Ugab, Al-Yarmouk, Al-Ein, and Al-Mamoun) in the western part of Mosul city, Iraq. Mosul city is surrounded from the western side of the right part by high areas represented by Atshan, Sheikh Ibrahim, Adayah, and Allan anticlines, this topographic situation imposes the wadis to pass the city towards the Tigris River. These wadis contain sediments derived from the exposed rocks of Fat’ha Formation hich consist of limestone, gypsum, and marl rocks in addition to the Quaternary deposits and soils. These wadis pass from residential areas with high population density and diverse activities (domestic, industrial, commercial, and agricultural), so these wadis are used as dumping sites for solid waste and wastewater. Twenty-five samples were analyzed chemically by X-ray fluorescence technique to determine the major and minor oxides, heavy elements in the German-Iraqi laboratory a the University of Baghdad. The organic matter and loss on ignition were performed in the geochemical laboratory at the department of geology in Mosul University. The major xides were; SiO2 (25.22-37.22) wt%, CaO (20.32-33.59) wt%, Al2 O3 (5.50-8.31) wt%, Fe2 O3 (3.86-6.10) wt%, MgO (2.15- .30) wt%, and CO2 (7.42-16.79) wt%, minor oxides were; TiO2 (0.52-0.78) wt%, Na2 O (0.37-1.08) wt%, K2 O (0.88-1.16) wt%, P2 O5 (0.12-0.63) wt%, SO3 (0.23-1.39) wt%, and Cl (0.01-0.05) wt%, Organic matter (OM) was (4.47-17.72) wt%. Heavy elements were; Cr (170-399) ppm, Ni (91-157) ppm, Cu (27-151) ppm, Zn (83-735) ppm, Pb (12-536) ppm, and As (4-10) ppm. The factor analysis sorts three main components representing 78,45 of total variance were (43,84, 27,39, 7,23) for the first, second and third factors, respectively, that reflect the controlling of elements distribution in the mineral groups of the sediments; the group of organic matter and secondary minerals, the clay minerals group, and the iron oxides group. In addition to the carbonate group. The geoaccumulation index (Igeo) indicates that in two industrial areas in Ugab wadi and Al-Yarmouk wadi there were highest concentrations of polluted elements in relation to the rest of wadis, and therefore these sites seemingly had high levels of pollution compared to other sites that appeared to have been moderately polluted. The maximum enrichment factor (EF) values were ordered as lead> zinc> chromium> copper> nickel> arsenic."}" data-sheets-userformat="{"2":15297,"3":{"1":0},"9":0,"10":1,"11":3,"12":0,"14":{"1":2,"2":0},"15":"Arial","16":8}">To assess the quality of sediment as it is an essential environmental indicator of water contamination due to sediments represent a permanent or temporary trap for various pollutants, a geochemical study was performed for sediments of four main wadis (Ugab, Al-Yarmouk, Al-Ein, and Al-Mamoun) in the western part of Mosul city, Iraq. Mosul city is surrounded from the western side of the right part by high areas represented by Atshan, Sheikh Ibrahim, Adayah, and Allan anticlines, this topographic situation imposes the wadis to pass the city towards the Tigris River. These wadis contain sediments derived from the exposed rocks of Fat’ha Formation hich consist of limestone, gypsum, and marl rocks in addition to the Quaternary deposits and soils. These wadis pass from residential areas with high population density and diverse activities (domestic, industrial, commercial, and agricultural), so these wadis are used as dumping sites for solid waste and wastewater. Twenty-five samples were analyzed chemically by X-ray fluorescence technique to determine the major and minor oxides, heavy elements in the German-Iraqi laboratory a the University of Baghdad. The organic matter and loss on ignition were performed in the geochemical laboratory at the department of geology in Mosul University. The major xides were; SiO2 (25.22-37.22) wt%, CaO (20.32-33.59) wt%, Al2 O3 (5.50-8.31) wt%, Fe2 O3 (3.86-6.10) wt%, MgO (2.15- .30) wt%, and CO2 (7.42-16.79) wt%, minor oxides were; TiO2 (0.52-0.78) wt%, Na2 O (0.37-1.08) wt%, K2 O (0.88-1.16) wt%, P2 O5 (0.12-0.63) wt%, SO3 (0.23-1.39) wt%, and Cl (0.01-0.05) wt%, Organic matter (OM) was (4.47-17.72) wt%. Heavy elements were; Cr (170-399) ppm, Ni (91-157) ppm, Cu (27-151) ppm, Zn (83-735) ppm, Pb (12-536) ppm, and As (4-10) ppm. The factor analysis sorts three main components representing 78,45 of total variance were (43,84, 27,39, 7,23) for the first, second and third factors, respectively, that reflect the controlling of elements distribution in the mineral groups of the sediments; the group of organic matter and secondary minerals, the clay minerals group, and the iron oxides group. In addition to the carbonate group. The geoaccumulation index (Igeo) indicates that in two industrial areas in Ugab wadi and Al-Yarmouk wadi there were highest concentrations of polluted elements in relation to the rest of wadis, and therefore these sites seemingly had high levels of pollution compared to other sites that appeared to have been moderately polluted. The maximum enrichment factor (EF) values were ordered as lead> zinc> chromium> copper> nickel> arsenic.